The role of public health advocacy in preventing and reducing gambling related harm: challenges, facilitators, and opportunities for change - David, J.; Thomas, S.; Randle, M.; Daube, Mike; Balandin, S. (Informa Healthcare, 2018)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. Background: Public health advocacy is important in preventing harm and promoting health in communities. There has been little research into public health advocacy strategies which address gambling related harms. This study aimed to identify the role of advocacy in gambling reform, challenges to gambling advocacy implementation, and strategies that could facilitate change. Methods: Semi-structured qualitative interviews were conducted with a sample of 50 stakeholders with backgrounds in gambling policy, research, health promotion, and advocacy. Participants were asked about how advocacy could be used to address gambling harm, and the range of barriers and facilitators for effective advocacy responses. A constant comparative method of analysis was used on the data. Results: While participants perceived that there was a role for advocacy in preventing and reducing gambling related harm, they discussed a range of challenges. These included restrictions associated with funding of research and services, the power of the gambling industry, and the role of stigma in preventing people with lived experience of gambling from speaking about their experiences. Participants also described a range of facilitators of public health advocacy approaches, including independent funding sources, reframing the ‘responsibility’ debate, developing opportunities and capacity for people with lived experience of harm, and developing broadly based coalitions to enable cohesive and consistent advocacy responses to gambling harm. Conclusion: There is a clear role for public health advocacy approaches aimed at preventing and reducing gambling harm. Future research could identify how advocacy strategies may be implemented as a part of a comprehensive public health approach to gambling reform.